2011
DOI: 10.1029/2011gl047533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cropland maximum light use efficiency using eddy flux measurements in North America and Europe

Abstract: [1] Croplands cover 12% of the ice-free land surface and play an important role in the global carbon cycle. Light use efficiency (LUE) models have often been employed to estimate the exchange of CO 2 between croplands and the atmosphere. A key parameter in these models is the maximum light use efficiency ("*), but estimates of "* vary by at least a factor 2. Here we used 12 agricultural eddyflux measurement sites in North America and Europe to constrain LUE models in general and "* in particular. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
7
27
1
2
Order By: Relevance
“…Though different from early studies using AVHRR data (Bradford et al, 2005;Lobell et al, 2002), our findings show agreement with recent studies (Bandaru et al, 2013;Chen et al, 2011;Guanter et al, 2014) and indicate that the field-derived ε * GPP values should be consistently used for large-scale modeling. In our results (Figures 2 and 5), it is clear that the underestimated MODIS GPP is largely due to the underestimated ε * GPP .…”
Section: Lue In Field Measurements and In Remote Sensing Modelssupporting
confidence: 81%
See 2 more Smart Citations
“…Though different from early studies using AVHRR data (Bradford et al, 2005;Lobell et al, 2002), our findings show agreement with recent studies (Bandaru et al, 2013;Chen et al, 2011;Guanter et al, 2014) and indicate that the field-derived ε * GPP values should be consistently used for large-scale modeling. In our results (Figures 2 and 5), it is clear that the underestimated MODIS GPP is largely due to the underestimated ε * GPP .…”
Section: Lue In Field Measurements and In Remote Sensing Modelssupporting
confidence: 81%
“…Most validation efforts for MODIS GPP have been made using eddy covariance data from flux tower measurements, and some studies suggest increasing the ε * GPP values in models to estimate cropland GPP (Chen et al, 2011;Zhang et al, 2008). On the other hand, some large-scale modeling studies identified overestimations of crop productivity in comparison with statistical inventory data when applying field-derived ε * GPP values (Lobell et al, 2002;Ruimy et al, 1994;Turner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…European crop yields today would be more than 16 % lower without access to improved varieties (the British Society of Plant Breeders, BSPB). The 2003 drought and heat in Europe reduced the terrestrial gross primary productivity (GPP) by 30 % (Ciais et al, 2005), while it was decreased by 15 % for cropland NPP in this study (Fig. 5i).…”
Section: Discussionmentioning
confidence: 91%
“…The importance of parameter calibration has been recognized and addressed by numerous modeling studies Chen et al, 2011;Crowther et al, 2016;Luo et al, 2016;Ogle et al, 2010;Peng et al, 2013). In addition, regional calibrated parameters are critical for global-scale modeling (Le Quéré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%